2011
DOI: 10.1177/0269216310391346
|View full text |Cite
|
Sign up to set email alerts
|

Challenging symptom profiles of life-limiting conditions in children: a survey of care professionals and families

Abstract: This paper reports on data from the initial phase of a UK-wide study exploring life-limiting conditions (LLCs) in children where, because of their rarity, little is understood regarding the significant symptom challenges of families and care professionals who support them. In this initial phase, care professionals (n=43) and families (n=16) completed a survey to identify which rare LLCs present symptom challenges and which individual symptoms prove difficult to manage. Findings led to the prioritization of muc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
49
0
2

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(57 citation statements)
references
References 18 publications
6
49
0
2
Order By: Relevance
“…This study’s findings reflect the wider literature looking at the impact of other types of life-limiting illness, which have also indicated that caring for someone with MPS has a wide impact across all dimensions of the family’s life [13, 14, 39–41]. These findings are again consistent with the literature on parents of children with other life-limiting conditions [13, 14, 39–41] and life-threatening conditions [42, 43].…”
Section: Discussionsupporting
confidence: 74%
See 2 more Smart Citations
“…This study’s findings reflect the wider literature looking at the impact of other types of life-limiting illness, which have also indicated that caring for someone with MPS has a wide impact across all dimensions of the family’s life [13, 14, 39–41]. These findings are again consistent with the literature on parents of children with other life-limiting conditions [13, 14, 39–41] and life-threatening conditions [42, 43].…”
Section: Discussionsupporting
confidence: 74%
“…They also reflected on issues of stigmatization and isolation in their experience of living with a child with a rare disorder. Even though the impact of child’s rare life-limiting illness on parents has been explored in a number of studies [13, 14, 18, 39–41] this study is the first of its nature that has explored the experience of Irish parents living with and caring for a child, adolescent and young adult across the full spectrum of MPS diagnoses.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…40,43,50 Another common subspecialty retrieved was that of pediatric neurodegenerative diseases. 41,42,52 Other studies retrieved examining the use of palliative care in child neurology included a study of children who had died of brain tumors, 49 and a compilation of short articles regarding palliative care for pediatric neurology patients, including review of pain in children with neuro-irritability and difficult-to-treat epilepsy. 51 The pediatric palliative care textbook reviewed included 1 chapter devoted exclusively to palliative care in neurologic illnesses, and a second chapter, to neuromuscular diseases.…”
Section: Identification Of Articles Regarding Palliative Care Within mentioning
confidence: 99%
“…Childhood leukodystrophies: a clinical perspective options [20,33,34]. These include medical, psychiatric, psychological, educational and other options.…”
Section: Reviewmentioning
confidence: 99%